Problems of Sport Biomechanics and Robotics. (13th February 2013) - Erdmann, Wlodzimierz S.
This paper presents many common areas of interest of different specialists. There are problems described from sport, biomechanics, sport biomechanics, sport engineering, robotics, biomechanics and robotics, sport biomechanics and robotics. There are many approaches to sport from different sciences and engineering. Robotics is a relatively new area and has had moderate attention from sport specialists. The aim of this paper is to present several areas necessary to develop sport robots based on biomechanics and also to present different types of sport robots: serving balls, helping to provide sports training, substituting humans during training, physically participating in competitions, physically participating in competitions against humans, serving as models of real sport performance, helping organizers of sport events and robot toys. Examples of the application of robots in sports communities are also given.